Strengthening Spiritual Values As A Strong Teacher Performance Basis - Hikmah, Neng Nur (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
There are many demands in the teaching profession, they must be smart, patient, compassionate, polite in appearance, friendly in speech, and highly dedicated. The hardest part about being a teacher is being an agent of change. The myriad of responsibilities are not only the responsibility of yourself, but also the organizers of the education unit. Schools need to create a support system for strengthening teacher performance, for example by cultivating spiritual values as the basis for carrying out their duties. This research was conducted to reveal the impact of strengthening spiritual values in improving teacher performance. This study uses qualitative methods with descriptive analysis. The object of the research was conducted in a public school in the city of South Tangerang. Data collection techniques were carried out by means of interviews and direct observation. Research correspondents are public school teachers who are civil servants. The results showed that the practice of religious values in work/teaching can affect the mental state and perceptions of teachers. There is a tendency to be wise in dealing with various problems, including the strengthening of self-commitment, to be able to carry out tasks as well as possible.